Marriage, a history : from obedience to intimacy or how love conquered marriage - Coontz, Stephanie (New York : Viking, 2005)
An analysis of the institution of marriage detailing how marriages have evolved from loveless unions to their current state, in
Introduction -- pt. 1: In search of traditional marriage. The radical idea of marrying for love -- The many meanings of marriage -- The invention of marriage -- pt. 2: The era of political marriage. Soap operas of the ancient world -- Something borrowed : the marital legacy of the classical world and early Christianity -- Playing the bishop, capturing the queen : aristocratic marriages in early medieval Europe -- How the other 95 percent wed : marriage among the common folk of the Middle Ages -- Something old, something new : Western European marriage at the dawn of the modern age -- pt. 3: The love revolution. From yoke mates to soul mates : emergence of the love match and the male provider marriage -- "Two birds within one nest" : sentimental marriage in nineteenth-century Europe and North America -- "A heaving volcano" : beneath the surface of Victorian marriage -- "The time when mountains move has come" : from sentimental to sexual marriage -- Making do, then making babies : marriage in the Great Depression and World War II -- The era of Ozzie and Harriet : the long decade of "traditional" marriage -- pt. 4: Courting disaster? : the collapse of universal and lifelong marriage. Winds of change : marriage in the 1960s and 1970s -- The perfect storm : the transformation of marriage at the end of the twentieth century -- Uncharted territory : how the transformation of marriage is changing our lives -- Conclusion : Better or worse? : the future of marriage.
Includes bibliographical references and index.
Keywords: Marriage -- History; Marriage; Huwelijk; Geschiedenis (vorm); Marriage; Social change; Interpersonal relations; Attitudes; History; Overseas item; Love; History